Anticipating mediated talks: Predicting the timing of mediation with disaggregated conflict dynamics. (March 2015) - Ruhe, Constantin
Research on mediation has shown that mediation can be an effective conflict management tool to contain intrastate conflicts, prevent escalation of low intensity conflicts, and foster de-escalation. But can ripe moments for conflict prevention effectively be anticipated? This article argues that the short-term conflict history provides a good predictor of the probability of mediation onset in low-intensity conflicts. It builds on an expected utility theory of mediation and states that conflict intensity is a primary indicator of whether a window of opportunity for mediation exists. Thereby, the article asserts that the direction of the effect is conditional on the respective probability of victory of each conflict party. The theory postulates that high conflict intensity only increases the probability of mediation onset when neither side is likely to prevail militarily. If one of the conflict parties has a high chance of a military success, then it will not regard conflict intensity as costly, since it can expect to impose these costs on its opponent. Under these circumstances the conflict parties will not be willing to engage in mediation. The article presents empirical support for this proposition. It uses temporally disaggregated data of low-intensity African conflicts from 1993 to 2004 and demonstrates that the theoretically motivated model predicts mediation onset with high accuracy. The results show that conflict dynamics are highly relevant covariates in predicting mediation. This selection process should be considered when the impact of mediation is evaluated.